2016
DOI: 10.1158/1055-9965.epi-16-0409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Collection Methods for Fecal Samples for Discovery Metabolomics in Epidemiologic Studies

Abstract: Background The gut metabolome may be associated with the incidence and progression of numerous diseases. The composition of the gut metabolome can be captured by measuring metabolite levels in the feces. However, there is little data describing the effect of fecal sample collection methods on metabolomic measures. Methods We collected fecal samples from eighteen volunteers using four methods: no solution, 95% ethanol, fecal occult blood test (FOBT) cards, and fecal immunochemical test (FIT). One set of sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 44 publications
4
85
0
Order By: Relevance
“…Similar approaches have also been used to study the reproducibility and stability of various fecal sampling methods. [35][36][37][38][39] Overall, the agreement between two fecal samples for all measures of alpha and beta diversity in healthy people and patients with 57 (0.28-0.86) 0.89 (0.81-0 which, to speculate, may be more pronounced in people with normal compared to slow colonic transit. The fecal microbiota, stool consistency, and colonic transit are known to be univariately associated with each other.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar approaches have also been used to study the reproducibility and stability of various fecal sampling methods. [35][36][37][38][39] Overall, the agreement between two fecal samples for all measures of alpha and beta diversity in healthy people and patients with 57 (0.28-0.86) 0.89 (0.81-0 which, to speculate, may be more pronounced in people with normal compared to slow colonic transit. The fecal microbiota, stool consistency, and colonic transit are known to be univariately associated with each other.…”
Section: Discussionmentioning
confidence: 91%
“…The reason we chose the ICC measure over other measures is that ICC is directly related to statistical power, a key issue in the study design. Similar approaches have also been used to study the reproducibility and stability of various fecal sampling methods …”
Section: Discussionmentioning
confidence: 99%
“…The easiest method for fecal storage is homogenization of the fresh stool sample by stirring with a sterile spatula directly in the delivery bag and then aliquoting a few milligrams to a few grams into feces tubes (i.e., Sarstedt) and storing at −80 °C . Le Galle et al .…”
Section: Sample Characteristics and Preanalytical Processingmentioning
confidence: 99%
“…Prestorage treatment and homogenization of fecal material is frequently done directly in ice‐cold phosphate‐buffered saline (PBS) by mixing representative volumes of feces with 2 volumes of PBS buffer . It has been shown that the addition of 95% ethanol, water/methanol, or twice distilled water tends to improve the overall recovery of fecal metabolites . Such prepared fecal slurry (fecal water) should be vortexed and ultracentrifuged at 35 000 × g for 2 h at 4 °C and the supernatant filtered, aliquoted, and stored at −80 °C.…”
Section: Sample Characteristics and Preanalytical Processingmentioning
confidence: 99%
“…12 N-methyl Alanine was identified in human fecal sample. 13 In the current era of omics studies, N-methylated amino acids have been reported as potential biomarkers for several diseases like prostate cancer, chronic kidney disease (CKD), and cardiovascular disease.…”
mentioning
confidence: 99%